2020
DOI: 10.2139/ssrn.3657535
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection Depends on Cellular Heparan Sulfate and ACE2

Abstract: Highlights d SARS-CoV-2 spike protein interacts with heparan sulfate and ACE2 through the RBD d Heparan sulfate promotes Spike-ACE2 interaction d SARS-CoV-2 infection is co-dependent on heparan sulfate and ACE2 d Heparin and non-anticoagulant derivatives block SARS-CoV-2 binding and infection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…EXTL2 encodes a glycosyltransferase involved in the chain elongation step of heparan sulfate (HS) biosynthesis [54,55]. Several heparan sulfate biosynthetic genes were also markedly enriched in other CRISPR knockout SARS-CoV-2 screens conducted in Huh7.5.1 cells [22,23] consistent with a recent report that SARS-CoV-2 infection is co-dependent on heparan sulfate and ACE2 [56]. Since HS is ubiquitously expressed on the surfaces and in the extracellular matrix of all cell types, EXTL2 may play a central pro-viral role through heparan sulfate production that may determine SARS-CoV-2 tropism.…”
Section: Sars-cov-2 Infectionsupporting
confidence: 73%
“…EXTL2 encodes a glycosyltransferase involved in the chain elongation step of heparan sulfate (HS) biosynthesis [54,55]. Several heparan sulfate biosynthetic genes were also markedly enriched in other CRISPR knockout SARS-CoV-2 screens conducted in Huh7.5.1 cells [22,23] consistent with a recent report that SARS-CoV-2 infection is co-dependent on heparan sulfate and ACE2 [56]. Since HS is ubiquitously expressed on the surfaces and in the extracellular matrix of all cell types, EXTL2 may play a central pro-viral role through heparan sulfate production that may determine SARS-CoV-2 tropism.…”
Section: Sars-cov-2 Infectionsupporting
confidence: 73%
“…These findings suggested that ACE2 expression levels may vary substantially between individuals or during an infection 81 or that SARS-CoV-2 can use alternate receptors to enter certain cell types (ie, the cell surface protein basigin (BSG, also known as CD147) 82 and CD26. 83 Several proteins have been recently identified to interact with SARS-CoV-2, including lectin receptors and multiple innate immune receptors, 84 heparan sulfate, 85 neuropilins, asialoglycoprotein receptor 1, and Kremen protein 1. 86 However, most of them lack virologyrelated evidence to support their roles as SARS-CoV-2 entry factors.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the current study show that enoxaparin effectively hinders the binding of NP to the cell surface in a dose-dependent manner and as a result significantly reduces the levels of C3b deposition, exposing another, yet unreported benefit of heparin analogs beneficial usage for COVID-19 management in addition to their known roles in clot prevention and inhibition of spike mediated virus entry (3941).…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, enoxaparin showed a dose dependent capacity to reduce cell surface binding of anti-NP IgGs (Figure 6D), in line with the observed NP displacement (Figure 6C). Accordingly, enoxaparin exhibited potent 15 rescue of A549 cells from anti-NP IgG driven complement deposition (Figure 6E, see also Supplementary Figure S5), revealing a novel, previously not yet considered mechanistic facet of immunological COVID-19 management with soluble heparin analogs, in addition to their previously reported benefits such as inhibition of SARS-CoV-2 entry (39,40) and prevention of blood clotting (41).…”
Section: Anti-np Iggs Activate the Classical Complement Pathway Targe...mentioning
confidence: 75%